Ensiklopedia perbidanan Melayu : sebuah perbendaharaan ilmu perubatan dan penjagaan kesihatan - Anisah Barakbah (Cheras, Kuala Lumpur : Utusan Publications & Distributors, 2007)
Encyclopedia of pregnancy, births, and maternal health care according to traditional Malay culture.
Includes bibliographical references (p. [344]) and index.
In Malay.